Optimalisasi Pemanfaatan Asam Jawa Lokal dalam Produksi Sirup di Desa Sopet sebagai Upaya Pemberdayaan Ekonomi Desa - Karina Nine Amalia; Riki Irawan; Zainatul Khasanah; Nanda Alfarosus Salsabila; Wahyu Setiawan (Jurnal Transformasi Digital Masyarakat (DIGIMAS), 2025)
Indonesia possesses abundant biodiversity and significant potential to enhance community welfare through the utilization of local resources. Tamarind (Tamarindus indica L.), which is abundant in Desa Sopet, Kecamatan Jangkar, Kabupaten Situbondo, is often sold in its raw form with low economic value. This research aims to increase the added value of tamarind by processing it into syrup. Activities were conducted from July to August 2024, involving local housewives, Srikandi Pujasera Sopet, and village officials in a socialization and training program for tamarind syrup production in Desa Sopet. The stages of the activity include a potential survey, product selection, syrup making, extension services, and sales at UMKM events. The results show that the pasteurization process and water reduction effectively extend the shelf life of the syrup and maintain its quality. This program is expected to increase the income and skills of the people of Desa Sopet, as well as strengthen the village economy with superior products that can compete in the local and national markets.